Slope Stability Analysis for Landslide in Road Preservation Working Packages Ende - Wolowaru and Junction – Kelimutu Sta 10+475 - Akbar, Fauzan; Lastiasih, Yudhi; Wahyudi, Herman; Junianto, Agustinus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The National Road Construction Agency (BPJN) in East Nusa Tenggara Province through the Satuan Kerja IV (Satker) has repaired some landslide points in the Ende – Wolowaru and Junction – Kelimutu Road Preservation working package. One of the landslide points that need treatment is at STA. 10+475. Based on survey and planning results from the Satker P2JN BPJN NTT, the most dominant factors that trigger landslides are geological conditions and high rainfall. Data from soil investigations at the landslide location at STA 10+475 after the landslide occurred showed that the soil was dominated by sandy clay. However, in their planning report, rainfall data was not found, therefore, it is needed to see whether there is an influence of rainwater infiltration at the location for causing landslides. This research aims to determine the causes of landslides including whether there is an influence of rainwater infiltration at the research location and the simulation results with the SLOPE/W and SEEP/W porgrams are proven to be correct. After simulating with the SEEP/W program, the slope safety factor which was 1.586 before the landslide occurred dropped to 0.883.